Evaluation of selected Culinary-Medicinal Mushrooms for Antioxidant and ACE inhibitory activities - Abdullah, Noorlidah; Ismail, Siti Marjiana; Aminudin, Norhaniza; Shuib, Adawiyah Suriza; Lau, Beng Fye (Hindawi, 2011)
Considering the importance of diet in prevention of oxidative stress-related diseases including hypertension, this study was undertaken to evaluate the in vitro antioxidant and ACE inhibitory activities of selected culinary-medicinal mushrooms extracted by boiling in water for 30 min. Antioxidant capacity was measured using the following assays: DPPH free radical scavenging activity, β-carotene bleaching, inhibition of lipid peroxidation, reducing power ability, and cupric ion reducing antioxidant capacity (CUPRAC). Antioxidant potential of each mushroom species was calculated based on the average percentages relative to quercetin and summarized as Antioxidant Index (AI). Ganoderma lucidum (30.1%), Schizophyllum commune (27.6%), and Hericium erinaceus (17.7%) showed relatively high AI. Total phenolics in these mushrooms varied between 6.19 to 63.51 mg GAE/g extract. In the ACE inhibitory assay, G. lucidum was shown to be the most potent species (IC(50) = 50 μg/mL). Based on our findings, culinary-medicinal mushrooms can be considered as potential source of dietary antioxidant and ACE inhibitory agents.